Financial Leverage, Innovation and Cournot Output: Limited Liability Effect Under Demand Uncertainty. Issue 4 (December 2022) - Saxena, Mohina; Bhattacharyya, Surajit
We address the strategic interdependence among capital structure, firm-level (process) innovation, and subsequent output decisions. In the backdrop of the limited liability effect, the interlinkage among financial and real variables is established through a three-stage game. The levered duopolist produces higher output and earns a larger profit than its unlevered counterpart. Even the industry output is higher when one of the duopolists is levered. However, if the levered duopolist undertakes investment in (process) innovation, then the debt-financed innovation induced output is larger than the innovation-led output of a completely equity financed firm. The levered innovative firm eventually becomes a monopolist by driving out the unlevered innovative duopolist. JEL Codes: D21, G32, L13, O31